Rapid detection of diagnostic targets using isothermal amplification and HyBeacon probes – A homogenous system for sequence-specific detection. Issue 2 (April 2015) - Howard, Rebecca L.; French, David J.; Richardson, James A.; O'Neill, Colette E.; Andreou, Michael P.; Brown, Tom; Clark, Duncan; Clarke, Ian N.; Holloway, John W.; Marsh, Peter; Debenham, Paul G.
Abstract: Isothermal amplification is a rapid, simple alternative to PCR, with amplification commonly detected using fluorescently labelled oligonucleotide probes, intercalating dyes or increased turbidity as a result of magnesium pyrophosphate generation. SNP identification is possible but requires either allele-specific primers or multiple dye-labelled probes, but further downstream processing is often required for allelic identification. Here we demonstrate that modification of common isothermal amplification methods by the addition of HyBeacon probes permits homogeneous sequence detection and discrimination by melting or annealing curve analysis. Furthermore, we demonstrate that isothermal amplification and sequence discrimination is possible directly from a crude sample such as an expressed buccal swab.